Comparative evaluation of triple antibiotic paste, propolis with moxifloxacin, and calcium hydroxide as intracanal medicaments against Streptococcus spp. and Enterococcus faecalis in type II diabetes mellitus patients: A randomized clinical trial - Chandrasekhar Tirukkolluru; Sophia Thakur (Wolters Kluwer Medknow Publications, 2019)
Aims: The antimicrobial efficacy of intracanal medicaments such as calcium hydroxide, propolis with moxifloxacin, and triple antibiotic paste (TAP) was assessed against Streptococcus spp. and Enterococcus faecalis in chronic apical periodontitis (AP) patients with Type II diabetes mellitus (DM). Settings and Design: This study design was a randomized clinical trial. Subjects and Methods: Forty-five Type II DM patients with single-rooted teeth diagnosed as AP were instrumented, randomly divided into three groups, and medicated with either TAP, propolis with moxifloxacin, or calcium hydroxide. Bacteriological samples obtained from the root canals after instrumentation (S1) in the first treatment session, and after medication (S2) in the second session 1 week later, were assessed for bacterial growth of E. faecalis and Streptococcus spp., by viable colony-forming unit counts. Statistical Analysis Used: Intragroup, intergroup, and pair-wise comparisons were done by Wilcoxon's signed ranked test, Kruskal-Wallis test, and Mann-Whitney test, respectively (P > 0.05). Results: The microbiological analysis showed a significant reduction in microbial count from (S1) to (S2) in all the study groups. However, intergroup comparisons revealed no significant difference in decrease of microbial load between all three groups at the end of 1 week. Conclusions: Within the limitations of the study, it was concluded that antimicrobial efficacy of TAP, propolis with moxifloxacin, and calcium hydroxide were comparable.